2004
DOI: 10.1161/01.cir.0000116210.70548.2a
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Ischemic Syndrome Evaluation

Abstract: Endorsed by the American College of Cardiology Foundation T he concomitant effects of aging, traditional risk factors, and a lack of endogenous estrogen promote the sequelae of arterial dysfunction, inflammation, and atheromatous plaque deposition in women. The challenges for improved diagnosis of coronary artery disease (CAD) in women include the more complex and multifactorial nature of the disease process; small artery size; and vascular and metabolic abnormalities that have yet to be thoroughly elucidated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Sex-related differences are becoming increasingly recognized as potentially important factors in atherosclerosis. 31 Whereas the prevalence of angina pectoris is similar among men and women, men have a higher incidence of MI and myocardial death than women at any age. 32 This divergence in sex ratios between angina pectoris and MI remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-related differences are becoming increasingly recognized as potentially important factors in atherosclerosis. 31 Whereas the prevalence of angina pectoris is similar among men and women, men have a higher incidence of MI and myocardial death than women at any age. 32 This divergence in sex ratios between angina pectoris and MI remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this observation are not apparent. Although epidemiological studies offer inconsistent evidence that the risk of diabetic retinopathy differs by sex, it has long been hypothesized that women are more susceptible to microvascular disease development than men (21). Moreover, hormonal changes associated with puberty have been suggested to contribute to the development of diabetic retinopathy (14,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…50,57 Emerging evidence also indicates that risk for coronary heart disease may be higher in women who were previously deemed 'low risk' by traditional risk factors. 57,58 In the Multi-Ethnic Study of Atherosclerosis cohort, retinopathy was shown to have significant correlation with increased coronary artery calcium scores. 59 Retinal arteriolar narrowing and decreased myocardial blood flow and perfusion reserve are also found to be closely linked.…”
Section: Genetic Associationsmentioning
confidence: 99%